A practical approach to design sulfur host material for lithium-sulfur batteries based on electrical conductivity and pore structure. (June 2021) - Kwon, Seongcho; Song, Hyeonjun; Çakmakçı, Nilüfer; Jeong, Youngjin
Graphical abstract: Abstract: Lithium-Sulfur (Li–S) batteries have emerged as one of the most promising batteries and as a next-generation energy source owing to their excellent gravimetric energy density. Sulfur is abundant in nature. Carbon materials have been widely used as sulfur host materials owing to their high electrical conductivity and large surface area. As the host materials highly influence the performance of Li–S batteries, their properties should be well designed. Therefore, understanding the significance of the properties of these materials as sulfur hosts is important in the practical design of electrodes. In this study, sulfur composite cathodes were fabricated using acetylene black (AB) and active carbon (AC) to investigate the effect of the carbon host material on the performance of the Li–S batteries. AB has a higher electrical conductivity and a smaller surface area compared to AC. The sulfur composite cathode with AB shows excellent cycling and kinetic performance compared with the sulfur composite cathode with AC, even though AC has a larger surface area, indicating that the cycling and kinetic performance of the Li–S battery is dominantly affected by the electrical conductivity of the carbon host.